A Study Of Adjustment Among The Adolescents Of Rural And Urban Areas - Sharma, Diwakar (International Journal of Rehabilitation and Special Education (IJRSE), 2022)
The objective of this research is to examine; how rural and urban students differ on adjustment. Adjustment Inventory for School Students by A.K.P. Sinha and R.P. Singh was administered on 400 male and females, randomly selected students from rural and urban secondary schools. The result of the study revealed that majority of boys and girls scored in average category on emotional, social, and educational adjustment. Gender relationships were found non-significant on all the aspects of school adjustment and self-confidence
Keywords: Adjustment; Adolescents; Urban Areas; Rural